Debating public administration : management challenges, choices, and opportunities - Durant, Robert F., 1949-; Durant, Jennifer R.S (ASPA series in public administration and public policy, 2012)
"Informed by a "5 R" framework (reconceptualizing purpose, redefining rationality, recapitalizing human assets, reengaging resources, and revitalizing democratic constitutionalism), this book bridges the gap between theory and practice. In this collection of articles revised for book format, the Durants expertly draw out themes, issues, problems, and prospects in their preface and section introductions. Bulleted lessons and practical take-aways are also added for the busy practitioner and researcher. This book is a 'one stop shop' for cross-disciplinary, cross-sectoral, and cross-professional exchanges on contemporary challenges, choices, and opportunities facing public administrators today"--